Effect of a statistical outlier in potency bioassays. (15th August 2018) - Sondag, Perceval; Zeng, Lingmin; Yu, Binbing; Rousseau, Réjane; Boulanger, Bruno; Yang, Harry; Novick, Steven
Abstract : The USP<1032> guidelines recommend the screening of bioassay data for outliers prior to performing a relative potency (RP) analysis. The guidelines, however, do not offer advice on the size or type of outlier that should be removed prior to model fitting and calculation of RP. Computer simulation was used to investigate the consequences of ignoring the USP<1032> guidance to remove outliers. For biotherapeutics and vaccines, outliers in potency data may result in the false acceptance/rejection of a bad/good lot of drug product. Biological activity, measured through a potency bioassay, is considered a critical quality attribute in manufacturing. If the concentration‐response potency curve of a test sample is deemed to be similar in shape to that of the reference standard, the curves are said to exhibit constant RP, an essential criterion for the interpretation of a RP. One or more outliers in the concentration‐response data, however, may result in a failure to declare similarity or may yield a biased RP estimate. Concentration‐response curves for test and reference were computer generated with constant RP from four‐parameter logistic curves. Single outlier, multiple outlier, and whole‐curve outlier scenarios were explored for their effects on the similarity testing and on the RP estimation. Though the simulations point to situations for which outlier removal is unnecessary, the results generally support the USP<1032> recommendation and illustrate the impact on the RP calculation when application of outlier removal procedures are discounted.